Ofatumumab: a novel monoclonal anti-CD20 antibody - Thomas S Lin (Dove Medical Press, 2010)
Thomas S LinGlaxoSmithKline Oncology R&D, Collegeville, PA, USAAbstract: Ofatumumab, a novel humanized monoclonal anti-CD20 antibody, was recently approved by the FDA for the treatment of fludarabine and alemtuzumab refractory chronic lymphocytic leukemia (CLL). Ofatumumab effectively induces complement-dependent cytotoxicity (CDC) in vitro, and recent studies demonstrated that ofatumumab also effectively mediates antibody-dependent cellular cytotoxicity (ADCC). Pharmacokinetic studies indicated that increased exposure to the antibody correlated with improved clinical outcome in CLL. Thus, pharmacogenomics may be important in identifying which patients are more likely to respond to ofatumumab therapy, although such studies have not yet been performed. Patients with the high-affinity FCGR3a 158 V/V polymorphism may be more likely to respond to therapy, if ADCC is the primary in vivo mechanism of action of ofatumumab. Patients with increased expression of the complement defense proteins CD55 and CD59 may be less likely to respond if ofatumumab works in vivo primarily via CDC. Patients with increased metabolism and clearance of ofatumumab may have lower exposure and be less likely to respond clinically. Thus, pharmacogenomics may determine the responsiveness of patients to ofatumumab therapy.Keywords: monoclonal antibody, CD20, CLL, NHL, lymphoma